Investigating the thermal stability of irradiation-induced damage in a zirconium alloy with novel in situ techniques. (15th February 2018) - Topping, M.; Ungár, T.; Race, C.P.; Harte, A.; Garner, A.; Baxter, F.; Dumbill, S.; Frankel, P.; Preuss, M.
Abstract: Zr alloys exhibit irradiation-induced growth and hardening which is associated with the defects and dislocation loops that form during irradiation. In this study, state-of-the-art in-situ synchrotron X-ray diffraction (SXRD) and transmission electron microscopy (TEM) techniques were used to investigate the stability of dislocation loops in two proton-irradiated Zr-Fe binary alloys in real time. Complementary data from both techniques show rapid annealing of a-loops occurs between 300 °C and 450 °C. Line profile analysis was performed on the SXRD patterns using the convoluted multiple whole profile analysis tool, to calculate the change in a-loop line density as a function of post-irradiation heat treatment temperature and time. At temperatures below 300 °C, no significant decrease in a-loop density was detected when held for 1 h at temperature. From this SXRD experiment, we calculate the effective activation energy for the annealing process as 0.46 eV. On-axis in-situ STEM imaging was used to directly observe a-loop mobility during heating cycles and confirm that a-loops begin to glide in the trace of the basal plane at ∼200 °C in a thin foil specimen. Such a-loop gliding events, leading to annihilation at the foil's surfaces, became more frequent between 300 and 450 °C. Graphical abstract: Image 1